Macroeconomics variables and its impact towards the gross domestic product in Malaysia / Mohammad Azrie Nordin - Nordin, Mohammad Azrie (2019)
Macroeconomic variables such as foreign direct investment, import, labor force household consumption expenditure and exchange rate was used as a framework to determine the impact toward gross domestic product in Malaysia from 1986 to 2016. In order to achieve the result, several method and test is used for example Unit root test which consider ADF and KPSS test followed by Ordinary Least Square(OLS) and diagnostic checking such as Autocorrelation test, Multicollinearity test and Heteroscedasticity test. Result show that there is a positive relationship between all variable toward gross domestic product and three out of five variables is significant toward gross domestic product which is exchange rate, import rate and household consumption expenditure. During multicollinearity test, these test achieve no multicollinearity after researcher omit the two variable that have tendency to faced multicollinearity problem which is import and labor force variable. Researcher manage to overcome heteroscedasticity problem after white test is done and there is no autocorrelation is achieve when researcher manage to do not reject null hypothesis. These finding may be vital for future economic growth and policy.